Adhesive sheet
By using thermally expandable microspheres and active energy ray curing adhesives in the adhesive sheet, the expansion and elastic modulus of the adhesive layer are controlled, and the inclination and poor picking of the processed products during the peeling process is solved. The problem of uniform peeling and good adhesive properties are achieved.
Patent Information
- Application Number
- CN202210328282.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-03-31
- Filing Date
- 2022-03-30
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-03-30
AI Technical Summary
During the peeling process, the existing adhesive sheets have uneven deformation of the surface of the adhesive layer, which leads to inclination and poor picking of the processed product, especially in the case of miniaturization of electronic components.
Using an adhesive layer containing thermally expandable microspheres, the adhesive expansion property when heated to the peak foaming temperature of the thermally expandable microspheres is controlled between 1.1 and 2, and the active energy ray-curing adhesive is combined with the Adhesive, optimize the elastic modulus and thermal expansion of the adhesive layer to achieve uniform shape changes and good peeling properties.
The uniform peeling of the processed article during peeling is achieved, avoiding tilt, improving the advantages of picking, and providing sufficient adhesion during the processing process.
Smart Images

Figure CN115141572B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an adhesive sheet. Background Art
[0002] As the adhesive sheet used for the purpose of temporarily fixing the processed product (for example, electronic component) in the process of manufacturing electronic components, it is known to have an adhesive sheet that shows adhesiveness when temporarily fixed, and shows the easy peelability of peelability when not needing to be fixed. As one of such adhesive sheets, the adhesive sheet (for example, patent documentation 1) that contains heat-expandable microspheres and constitutes in the adhesive layer is being studied. This adhesive sheet can show the desired adhesive force at a relatively low temperature represented by normal temperature to fix the processed product, and on the other hand, by heating, the heat-expandable microspheres expand, and produce concavo-convex on the adhesive layer surface, so that the adhesive force is reduced, and the processed product is easily peeled off.
[0003] After the workpiece is temporarily fixed as described above, the workpiece is sometimes picked up from above and transferred (for example, by adsorption transfer) during peeling. At this time, mainly due to the uneven deformation of the adhesive layer surface, there is a problem of the workpiece tilting and poor picking. Such a problem becomes more prominent as the workpiece (for example, electronic components) becomes smaller.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2001-131507 Summary of the invention
[0007] Problem that the invention aims to solve
[0008] The present invention has been made to solve the above-mentioned conventional problems, and an object of the present invention is to provide a PSA sheet having a PSA layer containing heat-expandable microspheres and excellent pick-up properties when an adherend is peeled off.
[0009] Solutions for solving problems
[0010] The adhesive sheet of the present invention comprises an adhesive layer containing heat-expandable microspheres, wherein the adhesive layer has an adhesive expansion property when heated to the foaming peak temperature of the heat-expandable microspheres (thickness of the adhesive layer when heated to the foaming peak temperature of the heat-expandable microspheres / thickness of the adhesive layer at 20° C.) of 1.1 to 2.
[0011] In one embodiment, the pressure-sensitive adhesive layer includes an active energy ray-curable pressure-sensitive adhesive.
[0012] In one embodiment, the active energy ray-curable adhesive includes a polymer and an oligomer as an active energy ray-reactive compound.
[0013] In one embodiment, the active energy ray-curable adhesive contains an active energy ray-reactive polymer.
[0014] In one embodiment, the active energy ray-curable adhesive contains a photopolymerization initiator, and the photopolymerization initiator is at least one selected from the group consisting of alkylphenone-based photopolymerization initiators, hydroxyacetophenone-based photopolymerization initiators, hydroxyketone-based photopolymerization initiators, aminoacetophenone-based photopolymerization initiators, and benzil ketal-based photopolymerization initiators.
[0015] In one embodiment, the active energy ray-curable adhesive contains a tackifier.
[0016] In one embodiment, the content ratio of the tackifier is 1 to 100 parts by weight based on 100 parts by weight of the polymer in the active energy ray-curable adhesive.
[0017] In one embodiment, the pressure-sensitive adhesive layer has an elastic modulus of 3.0 MPa to 400 MPa as measured by a nanoindentation method at a temperature 10° C. lower than a foaming start temperature of the expandable microspheres.
[0018] In one embodiment, the heat-expandable microspheres have a cumulative volume particle size D50 of 13 μm to 50 μm.
[0019] In one embodiment, the peak width of the particle size distribution of the heat-expandable microspheres is 20 μm or less.
[0020] In one embodiment, the content ratio of the heat-expandable microspheres is 5 to 50 parts by weight based on 100 parts by weight of the polymer in the binder.
[0021] In one embodiment, the initial adhesive force when the adhesive layer of the adhesive sheet is bonded to SUS304BA is 0.5 N / 20 mm to 25 N / 25 mm.
[0022] In one embodiment, the pressure-sensitive adhesive sheet further includes a substrate, and the pressure-sensitive adhesive layer is disposed on at least one side of the substrate.
[0023] According to another aspect of the present invention, a method for manufacturing an electronic component is provided, comprising: attaching the adhesive sheet to a device; irradiating the adhesive sheet with ultraviolet rays; and heating the adhesive sheet to peel the device from the adhesive sheet.
[0024] Effects of the Invention
[0025] According to the present invention, it is possible to provide a PSA sheet which includes a PSA layer containing heat-expandable microspheres and has excellent pick-up properties when an adherend is peeled off. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a schematic cross-sectional view of a pressure-sensitive adhesive sheet according to one embodiment of the present invention.
[0027] Description of Reference Numerals
[0028] 10 Adhesive layer
[0029] 20 Substrate
[0030] 30 Another adhesive layer
[0031] 100, 200, 300 adhesive sheet DETAILED DESCRIPTION
[0032] A. Overview of PSA Sheets
[0033] Figure 1 (a) is a schematic cross-sectional view of an adhesive sheet according to one embodiment of the present invention. The adhesive sheet 100 includes an adhesive layer 10. The adhesive sheet of the present invention may be composed of only the adhesive layer 10, or may further include any appropriate layer in addition to the adhesive layer.
[0034] Figure 1 (b) is a schematic cross-sectional view of a pressure-sensitive adhesive sheet according to another embodiment of the present invention. The pressure-sensitive adhesive sheet 200 further includes a substrate 20 , and the pressure-sensitive adhesive layer 10 is disposed on at least one side of the substrate 20 . Figure 1 (c) is a schematic cross-sectional view of an adhesive sheet according to another embodiment of the present invention. The adhesive sheet 300 comprises: an adhesive layer 10, and another adhesive layer 30 disposed on at least one side of the adhesive layer 10. A substrate 20 may be disposed between the adhesive layer 10 and the other adhesive layer 30 as shown in the example in the figure. Although not shown in the figure, the substrate may be omitted, and the adhesive sheet may be composed of the adhesive layer and the other adhesive layer. In addition, although not shown in the figure, the above-mentioned adhesive sheet may also include an elastic layer (hereinafter referred to as item E) that can impart elasticity to the above-mentioned adhesive sheet, a separator (hereinafter referred to as item F) disposed on the adhesive layer in a removable manner, etc. as a layer other than the adhesive layer. In addition, adhesive layers may also be disposed on both sides of the substrate.
[0035] In one embodiment, the pressure-sensitive adhesive layer is a pressure-sensitive adhesive layer that can be cured by irradiation with active energy rays. The curable pressure-sensitive adhesive layer can be composed of an active energy ray-curable pressure-sensitive adhesive.
[0036] The adhesive layer provided in the adhesive sheet of the present invention contains heat-expandable microspheres. The heat-expandable microspheres can be foamed at a specified temperature. For an adhesive layer containing such heat-expandable microspheres, the heat-expandable microspheres are foamed by heating, thereby generating concavoconvexities on the adhesive surface (i.e., the surface of the adhesive layer), thereby reducing or eliminating the adhesive force. When the adhesive sheet of the present invention is used as a temporary fixing sheet for processing, such as an electronic component (e.g., a printed circuit board), the workpiece is subjected to a specified processing (e.g., cutting) when the workpiece is subjected to temporary fixing. When the workpiece is peeled off from the adhesive sheet after processing, the adhesive force is reduced or eliminated by heating, thereby showing good peelability. In one embodiment, when the above-mentioned adhesive layer is curable, the adhesive layer is cured by active energy rays after the above-mentioned processing, and then heated to peel off the workpiece. By performing a bonding operation before curing, the adhesive sheet can be bonded with good concavoconvex tracking. In another embodiment, when the above-mentioned adhesive layer is curable, the bonding operation of the workpiece is performed after the adhesive layer is cured by active energy rays.
[0037] In the above-mentioned adhesive layer, the adhesive expansibility when heated to the foaming peak temperature of the heat-expandable microspheres is 1.1 to 2. In this specification, the adhesive expansibility is calculated by the thickness of the adhesive layer (single layer) at 20°C (initial thickness) and the thickness when heated to the foaming peak temperature of the heat-expandable microspheres (thickness at the foaming peak), and the calculation formula of [thickness at the foaming peak / initial thickness]. "The foaming peak temperature" refers to the temperature at which the thickness of the adhesive sheet becomes the maximum when the adhesive sheet is heated at a specified temperature (20°C to 300°C) for 1 minute. Here, "the temperature at which the thickness becomes the maximum" refers to the temperature at which the thickness becomes the maximum due to the expansion of the heat-expandable microspheres. At a temperature higher than the "temperature at which the thickness becomes the maximum", the adhesive tape becomes thinner again due to the contraction of the heat-expandable microspheres. In addition, the temperature at which the thickness of the adhesive layer is 110% relative to the thickness (initial thickness) of the adhesive layer at 20°C is set as the "foaming start temperature" described later. It should be noted that, in the case where the adhesive layer is curable, the "foaming peak temperature" and the "foaming start temperature" are both determined when the adhesive layer is irradiated with active energy rays (e.g., UV irradiation (1000 mJ / cm 2 )) is then heated for measurement.
[0038] In the present invention, by specifying the adhesive expansibility as described above, the shape change in the thickness direction of the adhesive layer during heating is suppressed, thereby improving the uniformity of the shape change. On the other hand, it is preferred to produce a tiny concave-convex shape caused by the heat-expandable microspheres. When using the adhesive sheet of the present invention having such characteristics, even when the workpiece is peeled off, the workpiece does not tilt, and as a result, poor pickup can be prevented. The adhesive expansibility when heated to the peak foaming temperature of the heat-expandable microspheres is preferably 1.1 to 1.8, more preferably 1.1 to 1.6, and further preferably 1.1 to 1.5. When it is in such a range, the above effect is significant. The adhesive expansibility can be controlled, for example, by the elastic modulus of the adhesive layer (for example, the elastic modulus obtained by the nanoindentation method at a temperature 10°C lower than the temperature at which the foaming starts), the size characteristics of the heat-expandable microspheres (for example, 50% particle size, particle size distribution), the amount of heat-expandable microspheres added, etc.
[0039] The initial adhesive force when the adhesive layer of the above adhesive sheet is attached to SUS304BA is preferably 0.5N / 20mm to 25N / 20mm, more preferably 1N / 20mm to 20N / 20mm, further preferably 1.5N / 20mm to 18N / 20mm, and particularly preferably 2N / 20mm to 15N / 20mm. When it is in such a range, for example, as a temporary fixing sheet used in the manufacture of electronic components, an adhesive sheet showing good adhesiveness can be obtained. The initial adhesive force in this specification refers to the adhesive force before the heat-expandable microspheres are foamed (in addition, before curing when the above adhesive layer is curable). The adhesive force is measured at 23°C by the method according to JIS Z 0237:2000 (lamination conditions: 2kg roller back and forth once, peeling speed: 300mm / min, peeling angle 180°).
[0040] In one embodiment, when the adhesive layer is curable, the adhesive sheet is irradiated with active energy rays (for example, with a cumulative light amount of 1000 mJ / cm 2 The adhesive strength at 23°C when the adhesive layer is attached to SUS304BA is preferably 0.1N / 20mm to 25N / 20mm, more preferably 0.2N / 20mm to 15N / 20mm, further preferably 0.2N / 20mm to 10N / 20mm, and particularly preferably 0.2N / 20mm to 5N / 20mm. As an example of the irradiation method of active energy rays, for example, after attaching the adhesive sheet to SUS304BA, an ultraviolet irradiation machine "UM810 (high-pressure mercury lamp light source)" (manufactured by Nitto Seiki Co., Ltd.) is used to irradiate from the adhesive sheet side with a cumulative light amount of 1000mJ / cm 2 The ultraviolet method.
[0041] The thickness of the pressure-sensitive adhesive sheet is preferably 30 μm to 500 μm, more preferably 40 μm to 300 μm, and even more preferably 50 μm to 200 μm.
[0042] In one embodiment, the adhesive sheet can be used as a fixing material for temporarily fixing the device when manufacturing an electronic component. In one embodiment, a method for manufacturing an electronic component is provided, which includes: a step of attaching the adhesive sheet to the device; a step of irradiating the adhesive sheet with ultraviolet rays; and then, a step of heating the adhesive sheet and peeling the device from the adhesive sheet. Preferably, the ultraviolet irradiation conditions in the "step of irradiating the adhesive sheet with ultraviolet rays" are adjusted to control the above-mentioned "adhesive expansion when heated to the peak foaming temperature of the heat-expandable microspheres". The ultraviolet irradiation amount is, for example, 10mJ / cm 2 ~1500mJ / cm 2 .
[0043] B. Adhesive layer
[0044] The adhesive layer contains an adhesive for imparting adhesiveness and heat-expandable microspheres.
[0045] The normal elastic modulus of the adhesive layer obtained by nanoindentation at 23° C. is preferably 1.0 MPa to 20.0 MPa, more preferably 3.0 MPa to 15.0 MPa. “Normal elastic modulus obtained by nanoindentation” refers to the elastic modulus before irradiation with active energy rays. The method for measuring the normal elastic modulus obtained by nanoindentation will be described later.
[0046] The elastic modulus obtained by nanoindentation at a temperature 10°C lower than the foaming start temperature of the heat-expandable microspheres of the above-mentioned adhesive layer is preferably 3.0MPa to 400MPa, more preferably 3.0MPa to 320MPa, further preferably 3.0MPa to 280MPa, and particularly preferably 6.0MPa to 200MPa. When it is in such a range, it is possible to obtain an adhesive sheet that will appropriately constrain the expansion of the heat-expandable microspheres, thereby preferably adjusting the adhesive expansion, preventing the inclination of the adherend during peeling, and showing sufficient heat-peelable properties. "The elastic modulus obtained by nanoindentation at a temperature 10°C lower than the foaming start temperature of the heat-expandable microspheres" can be adjusted by any appropriate method. For example, the elastic modulus can be set to an appropriate range by the structure of the adhesive component. In one embodiment, an adhesive layer is formed by using an active energy ray-curable adhesive as an adhesive, and the adhesive layer is irradiated with active energy rays (e.g., ultraviolet rays), thereby adjusting the "elastic modulus obtained by nanoindentation at a temperature 10°C lower than the foaming start temperature of the heat-expandable microspheres". In such an embodiment, as an active energy ray-curable adhesive, an adhesive containing an active energy ray-reactive compound (monomer or oligomer) or an active energy ray-reactive polymer is used, and the "elastic modulus obtained by the nanoindentation method at a temperature 10°C lower than the foaming starting temperature of the heat-expandable microspheres" can be adjusted by the amount of carbon-carbon multiple bonds in these compounds, the amount of adhesive added, the amount of active energy ray irradiation, etc.
[0047] The thickness of the pressure-sensitive adhesive layer is preferably 5 μm to 200 μm, more preferably 15 μm to 100 μm, further preferably 20 μm to 60 μm, and particularly preferably 25 μm to 45 μm.
[0048] The surface roughness Ra of the adhesive layer before the heat-expandable microspheres are foamed at an ambient temperature of 25°C is preferably 500nm or less, more preferably 400nm or less, and further preferably 300nm or less. When it is such a range, an adhesive sheet that can reduce the concavoconvexity generated on the bonding surface of the adherend can be obtained. It should be noted that the surface roughness Ra can be set to an appropriate value by adjusting the content, average particle size, etc. of the heat-expandable microspheres contained in the adhesive layer. The surface roughness Ra can be measured according to JIS B 0601:1994.
[0049] The adhesive sheet of the present invention is heated to foam the heat-expandable microspheres, and the surface roughness Ra of the adhesive layer is preferably 1 μm or more, more preferably 3 μm or more. When it is in such a range, it is possible to obtain an adhesive sheet in which the adhesive force is reduced or disappears after heating, thereby making it easy to peel off the adherend. It should be noted that, here, the surface roughness Ra of the adhesive layer refers to the surface roughness Ra of the adhesive layer after heating in a state without an adherend.
[0050] B-1. Adhesive
[0051] As the adhesive constituting the above-mentioned adhesive layer, any appropriate adhesive can be used as long as the effect of the present invention can be obtained. In one embodiment, as the above-mentioned adhesive, a curable adhesive is used, and preferably an active energy ray curable adhesive is used. In another embodiment, as the above-mentioned adhesive, a pressure-sensitive adhesive is used. As the pressure-sensitive adhesive, for example, acrylic adhesives, rubber adhesives, etc. can be cited. Preferably, a curable adhesive is used. When using a curable adhesive, the adhesive expansion can be preferably controlled.
[0052] (Active energy ray-curable adhesive)
[0053] As the above-mentioned active energy ray-curable adhesive, for example, there can be mentioned the adhesives described in UV curing system (Kato Kiyoshi, published by Comprehensive Technology Center, (1989)), photocuring technology (Technical Information Co-edited (2000)), Japanese Patent Publication No. 2003-292916, Japanese Patent No. 4151850, etc. More specifically, there can be mentioned an adhesive (R1) containing a polymer as a masterbatch and an active energy ray-reactive compound (monomer or oligomer), an adhesive (R2) containing an active energy ray-reactive polymer, etc. In one embodiment, the adhesive (R1) contains a polymer and an oligomer as an active energy ray-reactive compound.
[0054] Examples of the polymer used as the masterbatch include rubber polymers such as natural rubber, polyisobutylene rubber, styrene-butadiene rubber, styrene-isoprene-styrene block copolymer rubber, recycled rubber, butyl rubber, polyisobutylene rubber, nitrile rubber (NBR), silicone polymers, acrylic polymers, etc. These polymers may be used alone or in combination of two or more.
[0055] As the above-mentioned active energy ray reactive compound, for example, photoreactive monomers or oligomers containing functional groups with carbon-carbon multiple bonds such as multiple acryloyl, methacryloyl, vinyl, allyl, ethynyl, etc. can be enumerated. Wherein, preferably use the compound with ethylenically unsaturated functional groups, more preferably use the (meth) acrylic acid compounds with ethylenically unsaturated functional groups. The compound with ethylenically unsaturated functional groups easily utilizes ultraviolet rays to generate free radicals, so if the compound is used, it is possible to form an adhesive layer that can be cured in a short time. In addition, if the (meth) acrylic acid compounds with ethylenically unsaturated functional groups are used, it is possible to form an adhesive layer with appropriate hardness (specifically, the hardness that heat-expandable microspheres can be well foamed) after curing. Specific examples of photoreactive monomers or oligomers include (meth)acryloyl compounds such as urethane oligomers, urethane (meth)acrylates, trimethylolpropane tri(meth)acrylates, tetramethylolmethane tetra(meth)acrylates, pentaerythritol tri(meth)acrylates, pentaerythritol tetra(meth)acrylates, dipentaerythritol monohydroxypenta(meth)acrylates, dipentaerythritol hexa(meth)acrylates, 1,4-butanediol di(meth)acrylates, 1,6-butanediol di(meth)acrylates, and polyethylene glycol di(meth)acrylates; dimers to pentamers of the (meth)acryloyl compounds; and the like. These compounds may be used alone or in combination of two or more. In addition, the number of functional groups in the active energy ray-reactive compound may be only one or more. When there are two or more functional groups, it becomes easier to control the properties of the adhesive layer. It should be noted that in this specification, an oligomer refers to a compound having a molecular weight of less than 3.0×10 4 The molecular weight of the oligomer is preferably greater than 100, preferably 1.0×10 4 As the molecular weight of the oligomer, a weight average molecular weight (Mw) calculated based on standard polystyrene determined by gel permeation chromatography (GPC) or a molecular weight calculated from a chemical formula is used.
[0056] When an oligomer is used as the active energy ray reactive compound, the number of functional groups per molecule of the oligomer (the number of functional groups having carbon-carbon multiple bonds) is preferably 7 or more, more preferably 8 or more, further preferably 9 or more, and particularly preferably 10 or more. In such a range, the elastic modulus is preferably adjusted, and an adhesive layer that can exhibit a preferred adhesive expansion property can be obtained. The upper limit of the number of functional groups is preferably 20.
[0057] In addition, as the active energy ray reactive compound, monomers such as epoxidized butadiene, glycidyl methacrylate, acrylamide, vinyl siloxane, or oligomers thereof can be used. The adhesive (R1) containing these compounds can be cured by high energy rays such as ultraviolet rays and electron beams.
[0058] Furthermore, as the above-mentioned active energy ray reactive compound, a mixture of organic salts such as onium salts and compounds having multiple heterocycles in the molecule can be used. For this mixture, by the irradiation of active energy rays (for example, ultraviolet rays, electron beams), organic salts are cracked to generate ions, which become initiating species and cause the ring-opening reaction of heterocycles to form a 3D network structure. As the above-mentioned organic salts, for example, iodonium salts, phosphonium salts, antimony salts, sulfonium salts, borates, etc. can be cited. As the heterocycle in the compound having multiple heterocycles in the above-mentioned molecule, ethylene oxide, oxetane, oxolane (oxolane), thiirane (thiirane), aziridine, etc. can be cited.
[0059] In the adhesive (R1) comprising the polymer as the masterbatch and the active energy ray reactive compound, the content of the active energy ray reactive compound is preferably 5 to 200 parts by weight, more preferably 10 to 150 parts by weight, further preferably 10 to 100 parts by weight, and particularly preferably 10 to 80 parts by weight, relative to 100 parts by weight of the polymer as the masterbatch. In such a range, the elastic modulus is preferably adjusted, and an adhesive layer that can exhibit preferred adhesive expansion properties can be obtained. When the content of the active energy ray reactive compound is too high, there is a concern that the adherend may be contaminated.
[0060] As the active energy ray-reactive polymer, any appropriate polymer having a carbon-carbon double bond can be used.
[0061] In one embodiment, the polymer with carbon-carbon double bonds can be obtained by introducing carbon-carbon double bonds into a polymer not containing carbon-carbon double bonds by methods such as chemical modification. As a specific example of the method for introducing the above-mentioned carbon-carbon double bonds into a polymer not containing carbon-carbon double bonds, a method can be cited in which a monomer having a functional group A in a polymer not containing carbon-carbon double bonds is polymerized, and a compound (monomer or oligomer) having a functional group B and a carbon-carbon double bond that can react with the functional group A is reacted in a manner that the carbon-carbon double bond does not disappear (typically condensation, addition reaction). As an example of a combination of functional group A and functional group B, a combination of a carboxyl group and an epoxy group, a combination of a carboxyl group and an aziridine group, a combination of a hydroxyl group and an isocyanate group, etc. can be cited. Among them, from the viewpoint of reaction tracking, a combination of a hydroxyl group and an isocyanate group is preferred. In addition, as long as the combination of the functional groups A and B is a combination that can obtain a polymer having a carbon-carbon double bond, the functional group of one of the above combinations may be the functional group A and the other may be the functional group B, or the functional group of one of the above combinations may be the functional group B and the other may be the functional group A. Among them, a combination in which the polymer has a hydroxyl group and the above compound has an isocyanate group is preferred.
[0062] In addition, when the polymer not containing carbon-carbon double bond is vinyl alcohol polymer (for example, polyvinyl alcohol), the method of reacting vinyl alcohol polymer with halogenated vinyl such as vinyl bromide, halogenated allyl such as allyl bromide can also be cited as suitable example. The above reaction is carried out under suitable alkaline conditions. In addition, for example, the method of preparing the polymer with carbon-carbon double bond by using the microorganism producing polymer disclosed in Japanese Patent No. 4502363 can also be adopted. The conditions such as microorganism species and microorganism culture conditions in the method adopt the conditions recorded in the above-mentioned Japanese Patent Gazette or are suitably changed within the scope of the technical common sense of those skilled in the art, etc. to set.
[0063] The molar ratio (MA / MB) of the mole (MA) of the functional group A to the mole (MB) of the functional group B is preferably 0.2 or more, more preferably 0.5 or more, further preferably 0.7 or more, and particularly preferably 1 or more. When it is in such a range, a polymer having a carbon-carbon double bond can be obtained with good reactivity. In addition, the molar ratio (MA / MB) is preferably 2 or less, more preferably 1.5 or less, further preferably 1.3 or less, and particularly preferably 1.1 or less. In addition, from the viewpoint of increasing the contact opportunity between the functional group A and the functional group B, a compound having a functional group B containing a carbon-carbon double bond can be blended more. In this case, the molar ratio (MA / MB) is preferably set to less than 1 (preferably less than 0.99, more preferably less than 0.95). Alternatively, when the functional group A is used in other reactions (crosslinking reactions with crosslinking agents, etc.), the molar ratio (MA / MB) is preferably set to greater than 1. The amount of the compound having the functional group B is preferably 1 part by weight or more, more preferably 5 parts by weight or more, further preferably 10 parts by weight or more, further preferably 12 parts by weight or more, further preferably 15 parts by weight or more, further preferably 18 parts by weight or more, particularly preferably 21 parts by weight or more, and most preferably 23 parts by weight or more, within the range satisfying the above-mentioned molar ratio (MA / MB), relative to 100 parts by weight of the polymer having the functional group A. In addition, the amount of the compound having the functional group B is preferably 40 parts by weight or less, more preferably 35 parts by weight or less, further preferably 30 parts by weight or less, and particularly preferably 25 parts by weight or less, relative to 100 parts by weight of the polymer having the functional group A.
[0064] In addition, the polymer having a carbon-carbon double bond may be, for example, a diene polymer (e.g., a conjugated diene polymer). The diene polymer may be a polymer obtained by polymerizing or copolymerizing a diene (e.g., a conjugated diene). Examples of the diene polymer include butadiene polymers such as polybutadiene and styrene butadiene copolymers; isoprene polymers such as polyisoprene and styrene isoprene copolymers; chloroprene polymers such as polychloroprene; and the like.
[0065] In addition, for carbon-carbon double bonds, from the viewpoint of easy reactivity, external double bonds are more preferred than internal double bonds. Here, internal double bonds refer to double bonds that exist in a state of entering the interior of the main chain of a polymer or oligomer. The two carbon atoms of the carbon-carbon double bond constitute the main chain. In addition, external double bonds refer to double bonds that exist outside the molecular chain (e.g., main chain) of a polymer or oligomer. It should be noted that when a carbon-carbon double bond exists at the end of the main chain of a polymer or oligomer, the double bond is an external double bond.
[0066] The content ratio of the active energy ray reactive polymer (preferably a polymer having a carbon-carbon double bond) is preferably 10 parts by weight or more, more preferably 50 parts by weight or more, further preferably 70 parts by weight or more, further preferably 90 parts by weight or more, further preferably 95 parts by weight or more, further preferably 97 parts by weight or more, particularly preferably 99 parts by weight or more, and most preferably 99 to 100 parts by weight, relative to 100 parts by weight of the adhesive layer. When it is within such a range, an adhesive layer with a preferably adjusted elastic modulus can be obtained.
[0067] In one embodiment, as the above-mentioned active energy ray reactive polymer, there can be mentioned a polymer containing an active energy ray reactive functional group having a carbon-carbon multiple bond such as an acryloyl group, a methacryloyl group, a vinyl group, an allyl group, an ethynyl group, etc. It is preferred to use a compound (polymer) having an ethylenically unsaturated functional group, and more preferably a (meth) acrylic polymer having an acryloyl group or a methacryloyl group. As a specific example of a polymer having an active energy ray reactive functional group, there can be mentioned a polymer composed of a multifunctional (meth) acrylate, etc. The polymer composed of the multifunctional (meth) acrylate preferably has an alkyl ester having a carbon number of 4 or more in the side chain, more preferably an alkyl ester having a carbon number of 6 or more, further preferably an alkyl ester having a carbon number of 8 or more, particularly preferably an alkyl ester having a carbon number of 8 to 20, and most preferably an alkyl ester having a carbon number of 8 to 18. In the above-mentioned polymer, the content ratio of the structural unit having an alkyl ester having a carbon number of 4 or more as a side chain is preferably 30% by weight or more, more preferably 50% by weight to 80% by weight relative to all the structural units constituting the polymer.
[0068] The binder (R2) containing the active energy ray-reactive polymer may further contain the active energy ray-reactive compound (monomer or oligomer).
[0069] The above-mentioned active energy ray-curable adhesive can be cured by irradiation with active energy rays. In the adhesive sheet of the present invention, the adherend is attached before the adhesive is cured, and then the adhesive is cured by irradiation with active energy rays, thereby making the adherend close. As active energy rays, for example, gamma rays, ultraviolet rays, visible rays, infrared rays (heat rays), radio waves, alpha rays, beta rays, electron beams, plasma streams, ionizing rays, particle rays, etc. can be cited. The wavelength, irradiation amount and other conditions of the active energy rays can be set to any appropriate conditions according to the composition of the adhesive, etc. For example, the irradiation amount can be 10 to 1000 mJ / cm 2 The adhesive is cured by ultraviolet light.
[0070] (additive)
[0071] The adhesive may contain any appropriate additive as required. Examples of the additive include photopolymerization initiators, crosslinking agents, tackifiers, plasticizers, pigments, dyes, fillers, antioxidants, conductive materials, antistatic agents, ultraviolet light absorbers, light stabilizers, release regulators, softeners, surfactants, flame retardants, antioxidants, and the like.
[0072] In one embodiment, the adhesive comprises a tackifier. If the adhesive is made to contain a tackifier, an adhesive layer of the heat-expandable microspheres can be formed to be easily foamed. In addition, the adhesive sheet of the adherend tilting when the adhesive expansion property is preferably adjusted to prevent peeling can be obtained.
[0073] Any appropriate tackifier may be used as the tackifier. For example, a tackifier resin may be used as the tackifier. Specific examples of the tackifier resin include rosin-based tackifier resins (e.g., unmodified rosin, modified rosin, rosin phenol-based resins, rosin ester-based resins, etc.), terpene-based tackifier resins (e.g., terpene-based resins, terpene phenol-based resins, styrene-modified terpene-based resins, aromatic-modified terpene-based resins, hydrogenated terpene-based resins), hydrocarbon-based tackifier resins (e.g., aliphatic hydrocarbon resins, aliphatic cyclic hydrocarbon resins, aromatic hydrocarbon resins (e.g., styrene-based resins, xylene-based resins, etc.), aliphatic / aromatic petroleum resins, aliphatic / alicyclic petroleum resins, hydrogenated hydrocarbon resins, coumarone-based resins, coumarone-indene-based resins, etc.), phenol-based tackifier resins (e.g., alkylphenol-based resins, xylene formaldehyde-based resins, resol phenolic resins (resol), novolac, etc.), ketone-based tackifier resins, polyamide-based tackifier resins, epoxy-based tackifier resins, elastic-based tackifier resins, etc. Among them, rosin-based tackifier resins, terpene-based tackifier resins, or hydrocarbon-based tackifier resins (such as styrene-based resins) are preferred. The tackifiers may be used alone or in combination of two or more.
[0074] In one embodiment, a rosin-based tackifying resin and / or a terpene-based tackifying resin are used. These tackifying resins are particularly useful when used in combination with an adhesive containing a (meth) acrylic acid compound (the above-mentioned active energy ray-curable adhesive composed of an active energy ray-reactive compound or an active energy ray-reactive polymer of a (meth) acrylic acid system; the above-mentioned acrylic acid adhesive, etc.). In more detail, the above-mentioned tackifying resin has good compatibility with the adhesive containing a (meth) acrylic acid compound. Therefore, when the tackifying resin is used, it is not easy to produce a difference in adhesive force between small areas on the surface of the adhesive layer, and an adhesive sheet suitable for processing small adherends (processed objects) can be obtained.
[0075] The amount of the tackifier added is preferably 1 to 100 parts by weight, more preferably 1 to 80 parts by weight, further preferably 1 to 50 parts by weight, further preferably 5 to 30 parts by weight, particularly preferably 5 to 20 parts by weight, and most preferably 10 to 20 parts by weight, based on 100 parts by weight of the polymer in the adhesive.
[0076] The softening point of the tackifier is preferably 200° C. or less, more preferably 60° C. to 150° C. Within this range, a pressure-sensitive adhesive layer can be formed that is hard during adherend processing and becomes soft when heated to expand the heat-expandable microspheres.
[0077] As the above-mentioned photopolymerization initiator, any appropriate photopolymerization initiator can be used. Preferably, as the photopolymerization initiator, at least one selected from the group consisting of alkyl phenone photopolymerization initiators, hydroxyacetophenone photopolymerization initiators, hydroxyketone photopolymerization initiators, aminoacetophenone photopolymerization initiators and benzil ketal photopolymerization initiators. When using such a photopolymerization initiator, the control of the curing reaction becomes easy. More specifically, if the above-mentioned photopolymerization initiator is used, it is possible to obtain an adhesive layer that is cured only when irradiated with light in the ultraviolet region contained in special lighting and does not accidentally cure due to widely used light such as the light of the illumination, so it is easy to control the curing reaction of the adhesive layer. In addition, if the above-mentioned photopolymerization initiator is used, an adhesive layer that can be cured quickly and uniformly can be formed. If such an adhesive layer is formed, the heat-expandable microspheres can be foamed uniformly at the desired time, and the tilt of the adherend (chip) during heating can be prevented.
[0078] B-2. Heat-expandable microspheres
[0079] Heat-expandable microspheres are microspheres that can be expanded or foamed by heating. The adhesive sheet having an adhesive layer containing the heat-expandable microspheres generates concavities and convexities on the bonding surface by heating, thereby reducing the adhesive force, and therefore has sufficient adhesive force when adhesive force is required, and excellent peelability when peeling is required.
[0080] The content ratio of the above-mentioned heat-expandable microsphere can be suitably set according to the reduction of the desired adhesive force, etc. The content ratio of the heat-expandable microsphere is preferably 5 to 50 parts by weight, more preferably 10 to 50 parts by weight, further preferably 10 to 40 parts by weight, particularly preferably 10 to 30 parts by weight relative to 100 parts by weight of the polymer in the adhesive. When being such a scope, before the foaming of the heat-expandable microsphere, a smooth adhesive layer can be formed, after the foaming of the heat-expandable microsphere, an adhesive layer with good concavoconvex surface can be formed. In addition, the adhesive sheet of the tilted adherend when the adhesive expansion is preferably adjusted to prevent peeling can be obtained.
[0081] As above-mentioned heat-expandable microsphere, can use any suitable heat-expandable microsphere.As above-mentioned heat-expandable microsphere, for example, can use in having elastic shell and contain the microsphere of the material that expands easily by heating.Such heat-expandable microsphere can be manufactured by any suitable method, for example coagulation method, interfacial polymerization method etc.
[0082] Examples of substances that easily expand by heating include low-boiling-point liquids such as propane, propylene, butene, n-butane, isobutane, isopentane, neopentane, n-pentane, n-hexane, isohexane, heptane, octane, petroleum ether, methane halides, and tetraalkylsilane; azodicarbonamide that vaporizes by thermal decomposition; and the like.
[0083] As the material constituting the above shell, for example, there can be mentioned polymers composed of nitrile monomers such as acrylonitrile, methacrylonitrile, α-chloroacrylonitrile, α-ethoxyacrylonitrile, and butylenediconitrile; carboxylic acid monomers such as acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, and citraconic acid; vinylidene chloride; vinyl acetate; (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, isobornyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, and β-carboxyethyl acrylate; styrene monomers such as styrene, α-methylstyrene, and chlorostyrene; amide monomers such as acrylamide, substituted acrylamide, methacrylamide, and substituted methacrylamide; etc. The polymer composed of these monomers may be a homopolymer or a copolymer. Examples of the copolymer include vinylidene chloride-methyl methacrylate-acrylonitrile copolymer, methyl methacrylate-acrylonitrile-methacrylonitrile copolymer, methyl methacrylate-acrylonitrile copolymer, and acrylonitrile-methaconic acid copolymer.
[0084] As the heat-expandable microspheres, inorganic foaming agents or organic foaming agents can be used. Examples of the inorganic foaming agent include ammonium carbonate, ammonium bicarbonate, sodium bicarbonate, ammonium nitrite, sodium borohydride, and various azides. In addition, examples of organic foaming agents include chlorofluorinated alkane compounds such as trichloromonofluoromethane and dichloromonofluoromethane; azo compounds such as azobisisobutyronitrile, azodicarbonamide, and barium azodicarboxylate; hydrazine compounds such as p-toluenesulfonylhydrazine, diphenylsulfone-3,3'-disulfonylhydrazine, 4,4'-oxybis(benzenesulfonylhydrazine), and allylbis(sulfonylhydrazine); semicarbazide compounds such as p-toluenesulfonylsemicarbazide and 4,4'-oxybis(benzenesulfonylsemicarbazide); triazole compounds such as 5-morpholino-1,2,3,4-thiatriazole; N-nitroso compounds such as N,N'-dinitrosopentamethylenetetramine and N,N'-dimethyl-N,N'-dinitrosoterephthalamide; and the like.
[0085] The heat-expandable microspheres can be commercially available. Specific examples of the heat-expandable microspheres of commercial products include the trade names "Matsumoto Microsphere" (grades: F-30, F-30D, F-36D, F-36LV, F-50, F-50D, F-65, F-65D, FN-100SS, FN-100SSD, FN-180SS, FN-180SSD, F-190D, F-260D, F-2800D) manufactured by Matsumoto Oil & Fats Pharmaceutical Co., Ltd., and Japan Fillite Co., Ltd., "Expancel" (grades: 053-40, 031-40, 920-40, 909-80, 930-120), Kureha Chemical Co., Ltd., "DIFFORM" (grades: H750, H850, H1100, S2320D, S2640D, M330, M430, M520), Sekisui Chemical Co., Ltd., "ADVANCELL" (grades: EML101, EMH204, EHM301, EHM302, EHM303, EM304, EHM401, EM403, EM501), etc.
[0086] The volume cumulative particle diameter D50 (particle diameter of 50% of volume cumulative) of the above-mentioned heat-expandable microsphere is preferably 13μm~50μm, more preferably 13μm~40μm, further preferably 13μm~30μm, particularly preferably 15μm~30μm. When being such a range, the adhesive sheet of the tilt of the adherend that can be preferably adjusted to prevent peeling can be obtained.
[0087] The peak width of the particle size distribution of the above-mentioned heat-expandable microsphere is preferably below 20 μ m, more preferably below 18 μ m, and further preferably below 16 μ m. When the particle diameter is uniform, the uniformity of the expansion based on heating is also high. Therefore, if the heat-expandable microspheres showing the peak width of the particle size distribution as described above are used, the adhesive expansion can be preferably adjusted to prevent the inclined adhesive sheet of the adherend when peeling. The lower limit of the peak width of the particle size distribution of the heat-expandable microsphere is, for example, 10 μ m (preferably 8 μ m, more preferably 6 μ m). In this specification, "peak width of particle size distribution" is an index of the distribution width of the peak, which is calculated by the following method using D84% and D16% when the cumulative frequency of the peak is set to 100%.
[0088] Peak width (μm) = D84% (μm) - D16% (μm)
[0089] It should be noted that the above formula is only applicable to the peak with the largest area in a group of peaks represented by a continuous curve.
[0090] The heat-expandable microspheres have a moderate strength that does not break until the volume expansion ratio is preferably 5 times or more, more preferably 7 times or more, and further preferably 10 times or more. When using such heat-expandable microspheres, the adhesive force can be efficiently reduced by heat treatment.
[0091] C. Base material
[0092] As the above-mentioned substrate, for example, resin sheets, nonwoven fabrics, paper, metal foil, woven fabrics, rubber sheets, foam sheets, and laminates thereof (particularly laminates containing resin sheets) can be cited. As the resin constituting the resin sheet, for example, polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), polyethylene (PE), polypropylene (PP), ethylene-propylene copolymer, ethylene-vinyl acetate copolymer (EVA), polyamide (nylon), wholly aromatic polyamide (aramid), polyimide (PI), polyvinyl chloride (PVC), polyphenylene sulfide (PPS), fluorine resin, polyether ether ketone (PEEK), etc. can be cited. As nonwoven fabrics, nonwoven fabrics obtained from heat-resistant natural fibers such as nonwoven fabrics containing Manila hemp can be cited; synthetic resin nonwoven fabrics such as polypropylene resin nonwoven fabrics, polyethylene resin nonwoven fabrics, and ester resin nonwoven fabrics can be cited. As metal foils, copper foils, stainless steel foils, aluminum foils, etc. can be cited. Examples of paper include Japanese paper and kraft paper.
[0093] The thickness of the substrate can be set to any appropriate thickness according to the desired strength or flexibility, the purpose of use, etc. The thickness of the substrate is preferably 1000 μm or less, more preferably 1 μm to 1000 μm, further preferably 1 μm to 500 μm, particularly preferably 3 μm to 300 μm, and most preferably 5 μm to 250 μm.
[0094] The substrate may be subjected to a surface treatment, such as corona treatment, chromic acid treatment, ozone exposure, flame exposure, high voltage electric shock exposure, ionizing radiation treatment, primer coating treatment, and the like.
[0095] As the above-mentioned organic coating material, for example, the materials described in Plastic Hard Coating Material II (CMC Publishing, (2004)) can be cited. Preferably, a carbamate polymer is used, and more preferably, polyacrylic carbamate, polyester carbamate or their precursors are used. This is because the coating and application to the substrate is simple, and a variety of materials can be selected industrially and can be obtained inexpensively. The carbamate polymer is, for example, a polymer formed by a reaction mixture of an isocyanate monomer and an alcoholic hydroxyl-containing monomer (for example, a hydroxyl-containing acrylic compound or a hydroxyl-containing ester compound). The organic coating material may contain chain extenders such as polyamines, antioxidants, oxidation stabilizers, etc. as arbitrary additives. The thickness of the organic coating layer is not particularly limited, for example, about 0.1μm to 10μm is appropriate, preferably about 0.1μm to 5μm, and more preferably about 0.5μm to 5μm.
[0096] D. Another adhesive layer
[0097] As the above-mentioned other adhesive layer, any appropriate adhesive layer can be formed. As the adhesive forming the other adhesive layer, for example, rubber adhesive, acrylic adhesive, vinyl alkyl ether adhesive, silicone adhesive, polyester adhesive, polyamide adhesive, urethane adhesive, fluorine adhesive, styrene-diene block copolymer adhesive, etc. can be cited. The adhesive can be mixed with known or even commonly used additives such as plasticizers, fillers, surfactants, antioxidants, tackifiers, etc.
[0098] The thickness of the other adhesive layer is preferably 300 μm or less, more preferably 1 μm to 300 μm, and even more preferably 5 μm to 100 μm.
[0099] E. Elastic layer
[0100] The pressure-sensitive adhesive sheet of the present invention may further include an elastic layer. The elastic layer has a normal elastic modulus of 10.0 MPa or less at 23°C as determined by nanoindentation and is resistant to active energy rays (e.g., cumulative light intensity of 1000 mJ / cm 2 A layer having an elastic modulus of more than 10 MPa obtained by nanoindentation after irradiation with ultraviolet light (UV light). The normal elastic modulus of the elastic layer obtained by nanoindentation at 23°C is preferably 8 MPa or less, more preferably 5 MPa or less, and further preferably 3 MPa or less. The elastic layer can be arranged on one side of the adhesive layer. When the adhesive sheet has a substrate, the elastic layer can be arranged between the adhesive layer and the substrate. By having an elastic layer, the followability to the adherend is improved. In addition, the proportion of the adhesive layer in the adhesive sheet can be reduced, and as a result, an adhesive sheet that can be preferably deformed when heated can be obtained.
[0101] The elastic layer includes a base polymer, and as the base polymer, the polymer exemplified as the base polymer constituting the adhesive layer can be used. In one embodiment, the elastic layer may include natural rubber, synthetic rubber, synthetic resin, etc. As the synthetic rubber and synthetic resin, there can be cited nitrile, diene, and acrylic synthetic rubbers; thermoplastic elastomers such as polyolefins and polyesters; ethylene-vinyl acetate copolymers; polyurethanes; polybutadiene; soft polyvinyl chloride, etc. The base polymer constituting the elastic layer may be the same as or different from the base polymer forming the adhesive layer. It should be noted that the elastic layer and the adhesive layer can be distinguished by the difference in base polymers and / or the presence or absence of a foaming agent (the elastic layer does not contain a foaming agent). In more detail, in the case where the elastic layer and the adhesive layer are formed by different base polymers, and in the case where the interface between the elastic layer and the adhesive layer can be identified by cross-sectional observation, the boundary between the elastic layer and the adhesive layer is defined by the interface. In addition, in the case where the interface between the elastic layer and the adhesive layer cannot be identified by cross-sectional observation, the area where the foaming agent is observed by cross-sectional observation is the adhesive layer.
[0102] The elastic layer may contain any appropriate additives as required. Examples of such additives include crosslinking agents, vulcanizing agents, tackifying resins, plasticizers, softeners, fillers, antioxidants, etc. When a hard resin such as polyvinyl chloride is used as a base polymer, it is preferred to use a plasticizer and / or softener in combination to form an elastic layer having desired elasticity.
[0103] The thickness of the elastic layer is preferably 10 μm to 200 μm, more preferably 20 μm to 150 μm, and even more preferably 25 μm to 100 μm. Within such a range, the above-mentioned function of the elastic layer can be fully exhibited.
[0104] When the adhesive sheet is provided with an elastic layer, the thickness of the adhesive layer is preferably 60% or less, more preferably 50% or less, further preferably 45% or less, and particularly preferably 40% or less relative to the total thickness of the laminate containing the adhesive layer and the elastic layer. In such a range, the thickness of the adhesive layer, which has a greater influence on the deformation of the adhesive sheet, can be reduced, and an adhesive sheet having excellent balance between the followability, the deformation suppression of the adhesive layer, and the heat peelability can be obtained. In addition, relative to the total thickness of the laminate containing the adhesive layer and the elastic layer, the thickness of the adhesive layer is preferably 10% or more, more preferably 12% or more, further preferably 15% or more, and particularly preferably 20% or more. It should be noted that the "total thickness of the laminate containing the adhesive layer and the elastic layer" is the total thickness of the thickness of the single layer of the adhesive layer and the thickness of the single layer of the elastic layer. When the adhesive sheet is provided with a substrate, the "laminate containing the adhesive layer and the elastic layer" is a laminate containing the adhesive layer and the elastic layer arranged on the same side based on the substrate.
[0105] F. Isolate
[0106] The adhesive sheet of the present invention may further include a separator as required. At least one surface of the separator serves as a release surface and may be provided to protect the adhesive layer. The separator may be made of any appropriate material.
[0107] G. Method for producing adhesive sheet
[0108] Adhesive sheet of the present invention can be manufactured by any appropriate method.Adhesive sheet of the present invention can enumerate: for example, directly apply the method for the adhesive layer forming composition comprising adhesive and heat-expandable microsphere on substrate or apply adhesive layer forming composition on any appropriate matrix and transfer the formed coating layer to the method of substrate etc.Adhesive layer forming composition can comprise any appropriate solvent.In addition, after also can form adhesive coating layer by the composition comprising adhesive, heat-expandable microsphere is sprinkled on this adhesive coating layer, afterwards, embed this heat-expandable microsphere in this coating layer with laminating machine etc., thus form the adhesive layer comprising heat-expandable microsphere.
[0109] The content of the heat-expandable microspheres in the adhesive layer forming composition is preferably 5 to 95 wt %, more preferably 10 to 70 wt %, and further preferably 10 to 50 wt %, based on the solid content weight of the adhesive layer forming composition.
[0110] When the adhesive layer has the elastic layer, the elastic layer can be formed by, for example, applying a composition for forming an elastic layer on the substrate or on the adhesive layer.
[0111] As the coating method of each of the above-mentioned compositions, any appropriate coating method can be adopted. For example, it can be dried after coating to form each layer. As the coating method, for example, the coating method using a multi-function coater (Multi Coater), a die coater, a gravure coater, an applicator, etc. can be cited. As the drying method, for example, natural drying, heat drying, etc. can be cited. The heating temperature when heat drying is performed can be set to any appropriate temperature according to the characteristics of the material as the drying object.
[0112] [Example]
[0113] The present invention is described in detail below by way of examples, but the present invention is not limited to these examples. The evaluation method in the examples is as follows. It should be noted that in the following evaluation, the adhesive sheet from which the separator was peeled off was used. In addition, in the examples, "parts" and "%" are weight references unless otherwise specified.
[0114] (1) Initial adhesion
[0115] The adhesive sheet was cut into a size of 20 mm in width and 140 mm in length. According to JIS Z 0237:2009, a 2 kg roller was reciprocated once to attach the adhesive surface to the SUS304BA plate of the adherend to obtain a test sample. The test sample was set in a tensile testing machine with a constant temperature bath (manufactured by Shimadzu Corporation, trade name "Shimadzu Autograph AG-120kN"). Thereafter, the load when the adherend was peeled off from the adhesive sheet in the longitudinal direction under the conditions of peeling angle: 180° and tensile speed: 300 mm / min was measured, and the maximum load at this time (the maximum value of the load other than the peak at the beginning of the measurement) was obtained, and the value obtained by dividing the maximum load by the tape width was taken as the adhesive force (N / 20 mm width). It should be noted that the above operation was carried out in an atmosphere of temperature: 23°C and humidity: 65% RH.
[0116] (2) Adhesion after UV irradiation
[0117] The adhesive sheet was cut into a size of 20 mm in width and 140 mm in length, and the adhesive surface was attached to a SUS304BA plate of the adherend by rolling a 2 kg roller back and forth once according to JIS Z 0237:2009. After leaving it for 30 minutes, it was irradiated with ultraviolet rays (irradiation dose 1000 mJ / cm 2 ). The test sample is placed in a tensile testing machine with a thermostatic chamber (manufactured by Shimadzu Corporation, trade name "Shimadzu Autograph AG-120kN"). Thereafter, the load when the adherend is peeled off from the adhesive sheet in the length direction under the conditions of a peeling angle of 180° and a tensile speed of 300 mm / min is measured, and the maximum load at this time (the maximum value of the load other than the peak at the beginning of the measurement) is determined, and the value obtained by dividing the maximum load by the tape width is taken as the adhesive force (N / 20 mm width). It should be noted that the above operation is carried out in an atmosphere of temperature: 23°C and humidity: 65% RH.
[0118] (3) Adhesive expansion
[0119] The pressure-sensitive adhesive sheet was cut into a size of 20 mm in width and 140 mm in length to prepare a test piece.
[0120] A 10 mm thick heat-resistant glass (140 mm × 140 mm) was placed on a hot plate (Shamal Hot Plate "HHP-411") and preheated to a predetermined temperature. A test piece was placed on the hot plate, and a 10 mm thick heat-resistant glass was placed to cover the test piece. After the test piece was left as it was for 1 minute, the thickness of the test piece was measured with a direct-reading thickness gauge (dial gauge) to determine the thickness of the adhesive layer (thickness of the test piece (adhesive sheet) - thickness of the substrate).
[0121] The above-mentioned prescribed temperature is set to 20 ℃ to 300 ℃ in units of 10 ℃, and the above-mentioned operation is performed at each prescribed temperature. That is, a new test piece (discontinuous test piece) is used at each prescribed temperature to measure the thickness of the adhesive layer after heating. The result of carrying out these operations is that the temperature at which the adhesive layer thickness becomes the maximum is used as the foaming peak temperature. It should be noted that, as a result of carrying out the above-mentioned operation, the temperature at which the thickness of the adhesive layer becomes 110% relative to the thickness (initial thickness) of the adhesive layer at 20 ℃ is the foaming starting temperature of the heat-expandable microspheres.
[0122] The thickness of the adhesive layer was determined by the thickness at 20°C (initial thickness) and the thickness when heated to the foaming peak temperature (foaming peak thickness) using the formula [foaming peak thickness / initial thickness].
[0123] In the examples and comparative examples in which the adhesive layer is an active energy ray (ultraviolet) curable adhesive, UV irradiation was performed using an ultraviolet irradiation machine ("UM810 (high pressure mercury lamp light source)" (manufactured by Nitto Seiki Co., Ltd.) with a cumulative light dose of 1000 mJ / cm 2 ) to prepare the test piece.
[0124] (4) Elastic modulus of the adhesive layer obtained by nanoindentation at a temperature 10°C lower than the foaming start temperature of the heat-expandable microspheres
[0125] The elastic modulus obtained by the nanoindentation method refers to the elastic modulus obtained by continuously measuring the load and the indentation depth of the indenter when the indenter is pressed into the sample (e.g., the bonding surface) during loading and unloading. The elastic modulus obtained by the nanoindentation method is obtained as follows: the displacement-load hysteresis curve obtained by vertically pressing a diamond Berkovich-type (triangular pyramid-type) probe on the cut section of the measurement object layer is numerically processed using the software (triboscan) of the attached measurement device. In this specification, the elastic modulus is: the elastic modulus measured by a single indentation method at a specified temperature using a nanoindenter (Triboindenter TI-950 manufactured by Hysitron Inc.) under the measurement conditions of an indentation speed of about 500nm / sec, a pull-out speed of about 500nm / sec, and an indentation depth of about 3000nm.
[0126] (5) Chip scattering
[0127] A QFN lead frame (size: 125 mm × 65 mm; the bonding surface with the adhesive sheet is the resin surface) sealed with epoxy resin (manufactured by Hitachi Chemical Co., Ltd., trade name "CEL-9200HF9") was attached to the adhesive layer of each adhesive sheet, mounted and fixed on a 6-inch cutting ring, and cut into chips of 5 mm × 5 mm in size by a dicing machine (cutting-based cutting processing was performed). The number of chips that flew off during the cutting was calculated. At this time, the dicing blade used was ZH05-SD2000-N1-110-DD manufactured by DISCO. The moving speed of the dicing blade was set to 70 mm / s, and the rotation speed of the dicing blade was set to 50,000 / s.
[0128] The ratio (chip scattering rate) (%) of the number of chips peeled off from the adhesive tape (chip scattering) during the cutting process is calculated as an evaluation of the cutting processability. It should be noted that when all chips are attached to the adhesive tape and not peeled off, the chip scattering rate is 0% (i.e., the chip scattering rate is 0%). The number of chips cut is set as A0, the number of chips scattered is set as A, and the chip scattering rate X is calculated according to formula (1).
[0129] X=(A / A0)×100 (1)
[0130] The smaller the chip peeling ratio (chip scattering rate), the better the chip scattering prevention property is.
[0131] (6) Poor heating and peeling
[0132] After the above-mentioned cutting, a program temperature regulator (hot air dryer) (manufactured by Izumo Manufacturing Co., Ltd., "EP-K-300") is used to perform a heat treatment at the peak foaming temperature for 5 minutes. After the heat treatment, the adhesive tape is turned over in the air so that the top and bottom are reversed (the chip is at the bottom), and the chip is peeled off from the adhesive tape by natural falling, and the proportion of chips remaining on the sheet (chip residue) (%) is calculated. It should be noted that when all chips are peeled off and none remain on the adhesive tape, the chip residue is 0%. Therefore, after the heat treatment, the small amount of chips remaining after processing (small chip residue) means that the heat peeling property is good. The number of chips before peeling is set to B0, the number of chips remaining on the sheet after the heat peeling treatment is set to B, and the chip residue Y is calculated according to formula (2).
[0133] Y=(B / B0)×100 (2)
[0134] (7) Chip tilt
[0135] After the cutting in (5) above, use a program temperature regulator (hot air dryer) (manufactured by Izumo Manufacturing Co., Ltd., "EP-K-300") to perform a heat treatment at the peak bubble temperature for 5 minutes. After the heat treatment, visually confirm the inclination of the chip before implementing the above (6), and confirm the proportion of chip inclination after heat peeling (chip inclination) (%). It should be noted that when all chips are neat and not tilted, the chip inclination is 0%. Therefore, fewer chips that are tilted after the heat treatment (less chip inclination) means that the chip inclination is good. Let the number of chips before peeling be C0, and the number of chips tilted on the chip after the heat peeling treatment be C, and the chip inclination Z is calculated according to formula (3).
[0136] Z=(C / C0)×100 (3)
[0137] (8) Chip recovery failure (number)
[0138] The sum of the number of defects in (6) and the number of defects in (7) is defined as chip recovery failure.
[0139] (9) Particle size distribution peak width and particle size (D50) of heat-expandable microspheres
[0140] The adhesive sheet was fixed to a holder, and transmission images (1601 images for 0° to 360°) were continuously captured using X-ray CT (Zeiss, Xradia 520Versa, pixel size 0.3 μm / pixel, analysis software ImageJ).
[0141] Next, reconstruction is performed based on the obtained total transmission image to produce a tomographic image, a three-dimensional reconstruction image (TIF stack image) and a reconstructed cross-sectional image (three-view image). The foam is identified based on the obtained three-dimensional reconstruction image (TIF stack image) to calculate the volume cumulative particle size D50 and peak width.
[0142] [Production Example 1] Production of Polymer 1
[0143] After adding 30 parts by weight of 2-ethylhexyl acrylate, 70 parts by weight of ethyl acrylate, 5 parts by weight of methyl methacrylate, 5 parts by weight of hydroxyethyl acrylate, and 0.15 parts by weight of benzoyl peroxide as a polymerization initiator to toluene, the mixture was heated at 60° C. to obtain a toluene solution of an acrylic copolymer (polymer 1).
[0144] [Production Example 2] Production of Polymer 2
[0145] 100 parts by weight of 2-ethylhexyl acrylate, 25 parts by weight of acryloylmorpholine, 18 parts by weight of hydroxyethyl acrylate, and 0.25 parts by weight of benzoyl peroxide as a polymerization initiator were added to toluene, and then heated at 60° C. to obtain a toluene solution of an acrylic copolymer. 12 parts by weight of methacryloyloxyethyl isocyanate was added thereto to carry out an addition reaction, thereby obtaining a toluene solution of an acrylic copolymer having a carbon-carbon double bond (polymer 2).
[0146] [Production Example 3] Production of Polymer 3
[0147] 100 parts by weight of butyl acrylate, 5 parts by weight of acrylic acid, and 0.15 parts by weight of benzoyl peroxide as a polymerization initiator were added to toluene, and then heated at 60° C. to obtain a toluene solution of an acrylic copolymer (polymer 3).
[0148] [Production Example 4] Production of Polymer 4
[0149] 100 parts by weight of 2-ethylhexyl acrylate, 5 parts by weight of acrylic acid, and 0.15 parts by weight of benzoyl peroxide as a polymerization initiator were added to toluene, and then heated at 60° C. to obtain a toluene solution of an acrylic copolymer (polymer 4).
[0150] [Production Example 5] Production of Polymer 5
[0151] 100 parts by weight of butyl acrylate, 5 parts by weight of hydroxyethyl acrylate, and 0.15 parts by weight of benzoyl peroxide as a polymerization initiator were added to toluene, and then heated at 60° C. to obtain a toluene solution of an acrylic copolymer (polymer 5).
[0152] [Example 1]
[0153] (Preparation of elastic layer forming composition)
[0154] A toluene solution of polymer 1 (100 parts by weight), 1 part by weight of an isocyanate crosslinking agent (manufactured by Tosoh Corporation, trade name "CORONATE L"), 30 parts by weight of an active energy ray-reactive compound (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "Ultraviolet UV1700B"), 3 parts by weight of a photopolymerization initiator (manufactured by BASF, trade name "Omnirad127D"), and toluene were mixed to prepare a composition for forming an elastic layer.
[0155] (Preparation of Adhesive Layer-Forming Composition)
[0156] A toluene solution of polymer 1 (100 parts by weight), 0.5 parts by weight of an isocyanate crosslinking agent (manufactured by Tosoh Corporation, trade name "CORONATE L"), 30 parts by weight of an active energy ray-reactive compound (manufactured by Nippon Synthetic Chemical Co., Ltd., trade name "Ultraviolet UV1700B"), 3 parts by weight of a photopolymerization initiator (manufactured by BASF, trade name "Omnirad 127D"), 15 parts by weight of a tackifier (manufactured by Yasuhara Chemical Co., Ltd., trade name "Microace G125"), 35 parts by weight of heat-expandable microspheres (manufactured by AkzoNobel, trade name "092-40DU"), and toluene were mixed to prepare a composition for forming an adhesive layer.
[0157] (Manufacturing of Adhesive Tape)
[0158] A PET film (manufactured by Toray Industries, Inc., trade name "Lumirror S10", thickness: 25 μm) as a substrate was subjected to corona treatment, and the elastic layer-forming composition was applied thereto and dried to form an elastic layer (thickness: 50 μm) on the substrate.
[0159] The adhesive layer-forming composition was applied onto a polyethylene terephthalate film (MRF38, manufactured by Mitsubishi Chemical Polyester Film Co., Ltd.) having a silicone release agent-treated surface and dried to form an adhesive layer (30 μm) on the polyethylene terephthalate film.
[0160] The adhesive layer formed on the polyethylene terephthalate film was transferred to the elastic layer to obtain an adhesive tape having a substrate, an elastic layer and an adhesive layer in this order. The obtained adhesive tape was subjected to the above evaluations (1) to (9). The results are shown in the table.
[0161] [Examples 2 to 13, Comparative Examples 1 to 2]
[0162] The same operation as in Example 1 was performed except that the polymer, crosslinking agent, heat-expandable microspheres, active energy ray reactive compound and photopolymerization initiator shown in Table 1 were used in the blending amounts shown in Table 1, and the substrate shown in Table 1 was used. The obtained adhesive sheet was provided for the above evaluation. The results are shown in Table 1. It should be noted that the components used are as follows.
[0163] (Crosslinking agent)
[0164] ·CORONATE L: manufactured by Nippon Polyurethane Industry Co., Ltd., trade name "CORONATE L"
[0165] TETRAD C: Made by Mitsubishi Gas, trade name "TETRAD C"
[0166] (Heat-expandable microspheres)
[0167] 092-40DU: Made by AkzoNobel, trade name "092-40DU"
[0168] ·H-750D: Made by KUREHA CORPORATION, trade name "H-750D"
[0169] ·EML101: Made by Sekisui Chemical Co., Ltd., trade name "EML101"
[0170] ·F-50D: Made by Matsumoto Oil & Fats Pharmaceutical Co., Ltd., trade name "F-50D"
[0171] (Active energy ray-reactive compound)
[0172] UV1700B: manufactured by Nippon Synthetic Chemical Co., Ltd., trade name “purple light UV1700B”, molecular weight: 2000, C=C10 / 1 molecule)
[0173] UV3000B manufactured by Nippon Synthetic Chemical Co., Ltd., trade name “UV3000B”, molecular weight 18000, C=C2 / 1 molecule)
[0174] UV7605B (manufactured by Nippon Synthetic Chemical Co., Ltd., trade name “UV7605B”, molecular weight 1100, C=C6 / 1 molecule)
[0175] (Photopolymerization Initiator)
[0176] ·Omnirad127D: manufactured by BASF, trade name "Omnirad127D"
[0177] ·Omnirad651: manufactured by BASF, trade name "Omnirad651"
[0178] [Table 1]
[0179]
Claims
1. A pressure-sensitive adhesive sheet comprising a pressure-sensitive adhesive layer containing heat-expandable microspheres, In the adhesive layer, the adhesive expansion when heated to the foaming peak temperature of the heat-expandable microspheres, that is, the thickness of the adhesive layer when heated to the foaming peak temperature of the heat-expandable microspheres / the thickness of the adhesive layer at 20°C is 1.1 to 2, and the elastic modulus obtained by the nanoindentation method at a temperature 10°C lower than the foaming starting temperature of the expandable microspheres is 3.0 MPa to 400 MPa, in, The volume cumulative particle size D50 of the heat-expandable microspheres is 13 μm to 50 μm.
2. The adhesive sheet according to claim 1, wherein The adhesive layer includes an active energy ray-curable adhesive.
3. The adhesive sheet according to claim 2, wherein The active energy ray-curable adhesive includes a polymer and an oligomer as an active energy ray-reactive compound.
4. The adhesive sheet according to claim 2, wherein The active energy ray-curable adhesive includes an active energy ray-reactive polymer.
5. The adhesive sheet according to any one of claims 2 to 4, wherein The active energy ray-curable adhesive comprises a photopolymerization initiator, The photopolymerization initiator is at least one selected from the group consisting of alkylphenone-based photopolymerization initiators, hydroxyacetophenone-based photopolymerization initiators, hydroxyketone-based photopolymerization initiators, aminoacetophenone-based photopolymerization initiators, and benzyl ketal-based photopolymerization initiators.
6. The pressure-sensitive adhesive sheet according to any one of claims 2 to 4, wherein The active energy ray-curable adhesive contains a tackifier.
7. The adhesive sheet according to claim 5, wherein The active energy ray-curable adhesive contains a tackifier.
8. The adhesive sheet according to claim 6, wherein The content ratio of the tackifier is 1 to 100 parts by weight based on 100 parts by weight of the polymer in the active energy ray-curable adhesive.
9. The adhesive sheet according to claim 7, wherein The content ratio of the tackifier is 1 to 100 parts by weight based on 100 parts by weight of the polymer in the active energy ray-curable adhesive.
10. The pressure-sensitive adhesive sheet according to any one of claims 1 to 4, wherein The peak width of the particle size distribution of the heat-expandable microspheres is less than 20 μm.
11. The pressure-sensitive adhesive sheet according to any one of claims 1 to 4, wherein The content ratio of the heat-expandable microspheres is 5 to 50 parts by weight relative to 100 parts by weight of the polymer in the adhesive.
12. The pressure-sensitive adhesive sheet according to any one of claims 1 to 4, wherein The initial adhesive force when the adhesive layer of the adhesive sheet is bonded to SUS304BA is 0.5 N / 20 mm to 25 N / 25 mm.
13. The adhesive sheet according to any one of claims 1 to 4, further comprising a substrate, The adhesive layer is disposed on at least one side of the substrate.
14. A method for manufacturing an electronic component, comprising: A step of attaching the adhesive sheet according to claim 1 to a device; The step of irradiating the adhesive sheet with ultraviolet rays; and The adhesive sheet is heated to peel the device from the adhesive sheet.
Citation Information
Patent Citations
Thermally peeling type adhesive sheet
JP2001131507A
Method for processing adherend using adhesive sheet
JP2003292916A
Adhesive tape
CN108504298A